Supplementary data for: Chromosome-level genome assembly and circadian gene repertoire of the Patagonia blennie Eleginops maclovinus ... - Rivera-Colón, Angel (Zenodo, 2023)
This dataset contains the genome assembly and associated annotation of the Patagonian Blennie ( Eleginops maclovinus ), the closest extant taxon to the Antarctic notothenioid radiation. In addition to the characterization of the E. maclovinus genome, the dataset includes a description of circadian rhythm orthologs for E. maclovinus , other notothenenioid taxa, and teleost outgroups, as well as a copy of the bioinformatic scripts used for the assembly, annotation, and other downstream analysis. ... : All assembly and annotation files are gzipped, but are otherwise standard bioinformatic formats (i.e., FASTA for genome assembly and coding/amino acid sequences, GTF for annotation, AGP for scaffolding). In addition, bioinformatic scripts for data generation and analysis are in Python (*.py) or Bash (*.sh, but might require the installation of additional, open-source software (e.g., wtdbg2 , BRAKER ) See links for a description of the FASTA (http://www.ncbi.nlm.nih.gov/blast/fasta.shtml), and GTF (https://useast.ensembl.org/info/website/upload/gff.html), and AGP (https://www.ncbi.nlm.nih.gov/assembly/agp/AGP_Specification/) file format specifications. File format Specification File Suffix 1 Description *.fa Genome assembly in nucleotide FASTA format. *.agp Assembly structure in AGP format. *.gtf Genome annotation in GTF format. *.cds.fa Genomic sequence for all annotated protein-coding genes in nucleotide FASTA format. *.protein.fa Protein sequence for all annotated protein-coding genes in amino acid FASTA ...